The CD28 Transmembrane Domain Contains an Essential Dimerization Motif - Leddon, Scott A.; Fettis, Margaret M.; Abramo, Kristin; Kelly, Ryan; Oleksyn, David; Miller, Jim (Frontiers in Immunology, 2020)
CD28 plays a critical role in regulating immune responses both by enhancing effector T cell activation and differentiation and controlling the development and function of regulatory T cells. CD28 is expressed at the cell surface as a disulfide linked homodimer that is thought to bind ligand monovalently. How ligand binding triggers CD28 to induce intracellular signaling as well as the proximal signaling pathways that are induced are not well understood. In addition, recent data suggest inside-out signaling initiated by the T cell antigen receptor can enhance CD28 ligand binding, possibly by inducing a rearrangement of the CD28 dimer interface to allow for bivalent binding. To understand how possible conformational changes during ligand-induced receptor triggering and inside-out signaling are mediated, we examined the CD28 transmembrane domain. We identified an evolutionarily conserved YxxxxT motif that is shared with CTLA-4 and resembles the transmembrane dimerization motif within CD3. We show that the CD28 transmembrane domain can drive protein dimerization in a bacterial expression system at levels equivalent to the well know glycophorin A transmembrane dimerization motif. In addition, ectopic expression of the CD28 transmembrane domain into monomeric human CD25 can drive dimerization in murine T cells as detected by an increase in FRET by flow cytometry. Mutation of the polar YxxxxT motif to hydrophobic leucine residues (Y145L/T150L) attenuated CD28 transmembrane mediated dimerization in both the bacterial and mammalian assays. Introduction of the Y145L/T150L mutation of the CD28 transmembrane dimerization motif into the endogenous CD28 locus by CRISPR resulted in a dramatic loss in CD28 cell surface expression. These data suggest that under physiological conditions the YxxxxT dimerization motif within the CD28 transmembrane domain plays a critical role in the assembly and/or expression of stable CD28 dimers at the cell surface.